NEGOTIATING ISLAMIC BROADCASTING ETHICS: EXAMINING DIGITAL DA'WAH TRENDS AND THEOLOGICAL INTEGRITY ON TIKTOK AND INSTAGRAM REELS - Muhammad Riduan; Mohammad Rofiq; Ahmad Zinuddin (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2026)
Abstract The rapid digitalization of Islamic Broadcasting and Communication (KPI) has birthed the